Shedding new light on viruses: super-resolution microscopy for studying human immunodeficiency virus - Müller, Barbara; Heilemann, Mike (Trends in microbiology, 2013)
For more than 70 years electron microscopy (EM) techniques have played an important role in investigating structures of enveloped viruses. By contrast, use of fluorescence microscopy (FM) methods for this purpose was limited by the fact that the size of virus particles is generally around or below the diffraction limit of light microscopy. Various super-resolution (SR) fluorescence imaging techniques developed over the past two decades bypass the diffraction limit of light microscopy, allowing visualization of subviral details and bridging the gap between conventional FM and EM methods. We summarize here findings on human immunodeficiency virus (HIV-1) obtained using SR-FM techniques. Although the number of published studies is currently limited and some of the pioneering analyses also covered methodological or descriptive aspects, recent publications clearly indicate the potential to approach open questions in HIV-1 replication from a new angle.